Diseño de una máquina para destalonar llantas (2018)
In this project, the design of a tire bead breaker machine is proposed to help reduce the number of discarded tires on the streets of the city, at an affordable and efficient cost. For the completion of the degree project it was necessary to understand the specifications and requirements of the company Ruiz Fajardo Ingenieros SAS for the general design of the tire processing plant and specifically the machine to be designed, in this way an investigation was carried out on the existing machines in the market and thus determine the necessary modifications to comply with the parameters and requirements of the company. Once the first stage was completed, the systems and subsystems that make up the machine were defined, for which the basic parameters and the functional requirements established by the company were established. Three alternatives were raised and evaluated on the elevation subsystem, two mechanical alternatives were defined, and a hydraulic elevation system.